2019
DOI: 10.1021/acsnano.9b04970
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Graphene Oxide Nanocomposite Capable of Preventing the Evolution of Antimicrobial Resistance

Abstract: Antimicrobial resistance (AMR) is spreading worldwide and keeps evolving to adapt to antibiotics, causing increasing threats in clinics, which necessitates the exploration of antimicrobial agents for not only killing of resistant cells but also prevention of AMR progression. However, so far, there has been no effective approach. Herein, we designed lanthanum hydroxide and graphene oxide nanocomposites (La@GO) to confer a synergistic bactericidal effect in all tested resistant strains. More importantly, long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 45 publications
1
74
1
Order By: Relevance
“…In another study, silver bromide nanoparticle‐pyridinium polymeric composites adhered onto glass substrates and exhibited long‐term biocidal properties against airborne and waterborne bacteria . Furthermore, lanthanum hydroxide–graphene oxide nanocomposites (La@GO) conferred strong bactericidal effects on both wild‐type and antibiotic‐resistant E. coli , Lactobacillus crispatus , Staphylococcus aureus , and P. aeruginosa strains …”
Section: Introductionmentioning
confidence: 99%
“…In another study, silver bromide nanoparticle‐pyridinium polymeric composites adhered onto glass substrates and exhibited long‐term biocidal properties against airborne and waterborne bacteria . Furthermore, lanthanum hydroxide–graphene oxide nanocomposites (La@GO) conferred strong bactericidal effects on both wild‐type and antibiotic‐resistant E. coli , Lactobacillus crispatus , Staphylococcus aureus , and P. aeruginosa strains …”
Section: Introductionmentioning
confidence: 99%
“…While Fang et al identified substantial Pd NPs in Escherichia coli cells by energy dispersive spectroscopy (EDS) mapping, [56] graphene oxides were found to mainly associate with cell membranes. [72] For AgNPs, they were found to accumulate at the outer membrane and also in the periplasm, plasma membrane and cytoplasm of E. coli. [73] However, it is hard to rule out the possibility that precipitation of Ag ions in cytoplasm to form nanosized structures.…”
Section: Dermal Exposurementioning
confidence: 99%
“…After the depletion of free phosphates, the lanthanide ions may grab phosphates from phospholipids or proteins and induce lysosomal permeabilization or plasma membrane damages. [72] The recrystallization includes three stages: whisker, whisker growth, and maturation of urchin-shaped structures. This recrystallization process at physiological conditions was determined by the solubility of rare earth NPs in acidic lysosomes and precipitation of lanthanide phosphates (Figure 4).…”
Section: Recrystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene oxide (GO) nanoparticles (NPs) have been widely used in biomedical fields due to their physical and chemical properties, which make them useful for applications in as drug delivery [1,2], tumor photothermal therapy [3][4][5], bioimaging [6], tissue engineering [7,8], antimicrobial agents [9,10], biosensors [11][12][13][14]. At the same time, the risk of human contact has increased dramatically.…”
Section: Introductionmentioning
confidence: 99%